PUPUK ORGANIK CAIR KOMBINASI LIMBAH ENCENG GONDOK DAN BUAH BUSUK PADA TANAMAN KANGKUNG DARAT (Ipomea reptans) - Intan, Intan (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
Water hyacinth (Eichornia crassipes) is a type of aquatic plant that has a fast growth rate so it is referred to as a weed that disturbs water areas. Water hyacinth can be used as a liquid fertilizer that is useful against the needs of plant nutrients. Rotten fruits used by papaya, guava and banana are a mixture of making liquid organic fertilizer. This study was used to determine the effect of liquid organic fertilizer by combining water hyacinth plants and rotten fruit on ground kale plants (Ipomea reptans oil). The parameters measured were plant height and weight of ground water spinach plants on the day 7,14,21 and 28 days after planting, using 4 treatments with different concentrations namely P0 (without POC), P1 (100ml POC), P2 (200ml POC ), and P3 (300ml POC). The results of the analysis showed that it was significant (p <0.005) so that the manufacture of POC from water hyacinth waste and rotten fruit could increase growth in land kale plants (Ipomea reptans oil).